Strategi Nutrisi Pada Pasien Hiperglikemia di Intensive Care Unit (ICU): Scoping Review - Dadan Ramdani; A. Danang Asmara; Deris Riandi Setiawan; Stepanus Prihasto Septiawan (Universitas Pahlawan Tuanku Tambusai, 2025)
Hyperglycemia is a common condition in Intensive Care Unit (ICU) patients caused by metabolic stress and insulin resistance, which increases the risk of cardiovascular complications, organ dysfunction, and infections. Proper nutritional management plays a crucial role in controlling blood glucose levels in ICU patients. This study aims to explore various nutritional strategies for patients with hyperglycemia in the ICU. The method used is a scoping review of six articles published between 2014 and 2024, which include both enteral and parenteral nutrition. The analysis results show that enteral nutrition focuses on high protein intake, adequate fat, and carbohydrate restriction. Some studies also recommend consuming high-protein fruits to help control blood glucose levels. Parenteral nutrition with vitamin D3 and calcium has also been shown to influence glucose control. The conclusion of this study is that proper nutritional management can optimize blood glucose control in ICU patients and reduce the need for insulin. This research is expected to serve as a reference for healthcare professionals in designing more effective nutritional strategies for hyperglycemic patients in the ICU.